The three-tails approach as a new strategy to improve selectivity of action of sulphonamide inhibitors against tumour-associated carbonic anhydrase IX and XII - Alessandro Bonardi; Silvia Bua; Jacob Combs; Carrie Lomelino; Jacob Andring; Sameh Mohamed Osman; Alessandra Toti; Lorenzo Di Cesare Mannelli; Paola Gratteri; Carla Ghelardini; Robert McKenna; Alessio Nocentini; et al. (Taylor & Francis Group, 2022)
Human (h) carbonic anhydrase (CAs, EC 4.2.1.1) isoforms IX and XII were recently confirmed as anticancer targets against solid hypoxic tumours. The "three-tails approach" has been proposed as an extension of the forerunner "tail" and "dual-tail approach" to fully exploit the amino acid differences at the medium/outer active site rims among different hCAs and to obtain more isoform-selective inhibitors. Many three-tailed inhibitors (TTIs) showed higher selectivity against the tumour-associated isoforms hCA IX and XII with respect to the off-targets hCA I and II. X-ray crystallography studies were performed to investigate the binding mode of four TTIs in complex with a hCA IX mimic. The ability of the most potent and selective TTIs to reduce in vitro the viability of colon cancer (HT29), prostate adenocarcinoma (PC3), and breast cancer (ZR75-1) cell lines was evaluated in normoxic (21% O2) and hypoxic (3% O2) conditions demonstrating relevant anti-proliferative effects.